2000
DOI: 10.1542/peds.106.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Discharge Timing and Readmissions: California, 1992–1995

Abstract: One-night stays with adequate antenatal and postnatal care outside the hospital do not increase the risk of readmission for healthy, vaginally delivered infants born in California. However, the decision to discharge infants on the day of birth should be applied conservatively because of the increased risk of infant readmission associated with very early discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
98
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 13 publications
9
98
1
2
Order By: Relevance
“…2,4,12,19 Two previous studies responded to this difficulty by comparing deaths among newborns with stays of Ͻ30 hours to deaths among newborns with stays of 30 to 78 hours. 2,12 Following a previous study of newborn readmissions, 6 however, we estimated LOS in hours using the known hour of birth and number of nights stayed along with assumptions about the time of discharge.…”
Section: Estimation Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,12,19 Two previous studies responded to this difficulty by comparing deaths among newborns with stays of Ͻ30 hours to deaths among newborns with stays of 30 to 78 hours. 2,12 Following a previous study of newborn readmissions, 6 however, we estimated LOS in hours using the known hour of birth and number of nights stayed along with assumptions about the time of discharge.…”
Section: Estimation Strategymentioning
confidence: 99%
“…Several studies have found positive associations between short postpartum stays and neonatal hospital readmission. [2][3][4][5][6] There is also evidence that short stays increase neonatal mortality. Of the 4 million infants born in the United States each year, approximately 20 000 (5 of 1000) die during the neonatal period (ie, during the first 28 days of life), and another 10 000 die after the neonatal period but before their first birthday.…”
mentioning
confidence: 99%
“…Shorter hospital stays for uncomplicated vaginal births have medical, economic, and social benefits, 89,90 and they are indicative of better overall health of the mother and newborn. 91 We found that infants born to mothers receiving HBPB had significantly shorter birth hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Other frequently reported risk factors for readmission were Asian race, primiparity, associated maternal morbidities, shorter gestation or lower birth weight, instrumented vaginal delivery, and small size for gestational age. 13,[15][16][17][18] Close follow-up and better coordination of postdischarge care were important factors in decreasing the readmission rates. 13,17 Readiness for Discharge…”
Section: Risk Of Readmissionmentioning
confidence: 99%
“…13,[15][16][17][18] Close follow-up and better coordination of postdischarge care were important factors in decreasing the readmission rates. 13,17 Readiness for Discharge…”
Section: Risk Of Readmissionmentioning
confidence: 99%